Viagens feitas de Sons: contributos para uma (re)escrita de diásporas de mulheres imigrantes de leste em Portugal - Guerra, Paula (2021)
This article is a brief refl ection on the relationship between music and the identity representations of Romanian immigrant women in Portugal, namely in the Metropolitan Area of Porto (Porto, Maia, Valongo, Póvoa de Varzim and Vila Nova de Gaia). Starting from the assumption that music is a strong component of the daily life of these women, we highlight its relevance as a means of resistance, affi rmation and survival in their journey and reception in Portugal. Moreover, based on the application of a qualitative methodology, based on the completion of 20 life stories of Romanian women immigrants in Portugal, we conclude that there is a gap between what is the culture of origin and the culture of the host country: in the sense that multiculturalism and the sharing of tastes, aesthetics and memories of the context of origin are not emphasized. In fact, this aspect is all the more pressing when we think about the strong stigmatization and discrimination that these women suffer daily in a logic of symbolic - and sometimes physical - violence. Furthermore, music tends to be the means that unites them to their culture, their memories, their family and neighbourhood traditions, assuming itself as a powerful vehicle of identity reconstruction in overcoming daily difficulties.